2018
DOI: 10.1186/s13568-018-0721-1
|View full text |Cite
|
Sign up to set email alerts
|

High tetramethylpyrazine production by the endophytic bacterial Bacillus subtilis isolated from the traditional medicinal plant Ligusticum chuanxiong Hort.

Abstract: Tetramethylpyrazine (TMP) with significant protective effects on cardiovascular is the active ingredient of traditional Chinese medicine Rhizoma Chuanxiong (RC). However, many studies have reported the low content of TMP in RC. The endophytes of medicinal plants have the biosynthetic potential to produce the same or similar active metabolites as the host, while few reports were conducted to explore the endophytic bacteria of Ligusticum chuanxiong Hort. and its productive capacity for the important ingredient T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…This report illustrates two parameters by which C. glutamicum can be modified to produce tetra-methylpyrazine, TMP. Our highest final titers from batch and fed-batch production modes compare favorably with published titers from Bacillus subtilis (Xiao et al., 2014; Yin et al., 2018) and do not require a post-cultivation denaturing step to produce TMP . Unlike E .…”
Section: Discussionsupporting
confidence: 68%
“…This report illustrates two parameters by which C. glutamicum can be modified to produce tetra-methylpyrazine, TMP. Our highest final titers from batch and fed-batch production modes compare favorably with published titers from Bacillus subtilis (Xiao et al., 2014; Yin et al., 2018) and do not require a post-cultivation denaturing step to produce TMP . Unlike E .…”
Section: Discussionsupporting
confidence: 68%
“…It has been found that the endophytic fungi of L. chuanxiong are often significantly related to their active ingredients. For example, the content of ibutilide is significantly related to endophytes, such as Penicillium and Wardell , and Bacillus subtilis can secrete Ligustrazine ( Yin et al, 2018a , b , 2019 ). Therefore, endophytic fungi can affect the quality of the rhizome of L. chuanxiong by regulating the production of its secondary metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…According to the previous preliminary study of our research, a considerable yield of ligustrazine (10.69 g/L, 144 h) can be produced by the endophytic B.subtilis LB5, which was isolated from the fresh rhizome of Ligusticum chuanxiong Hort [24]. The yeast extract peptone glucose medium provided an excellent and nutritious growing environment for the fermentation of B. subtilis LB5.…”
Section: Introductionmentioning
confidence: 90%